Microbial metabolites in tumor metabolic reprogramming and immunotherapy: new insights - Wang, Yi; Huang, Dan; Wang, Rongrong; Yin, Jiaojiao; Pei, Jianying; Zhang, Chong (Frontiers in Cellular and Infection Microbiology, 2025)
Gut microbiota and intratumoral microbiota have been recognized as critical regulators of tumor initiation and progression, with their metabolites exerting multifaceted effects on cancer development. This review systematically summarizes the roles and mechanistic classifications of microbial metabolites in tumor metabolic reprogramming, highlighting three principal regulatory layers: direct modulation of metabolic enzyme activity, regulation via signaling pathways, and immunometabolic modulation. Furthermore, it discusses the potential of microbial metabolites in regulating immune cell metabolism and enhancing immunotherapeutic efficacy, alongside summarizing the progress of relevant clinical studies. Finally, the review emphasizes that despite significant advances, current research still faces multiple challenges. Future investigations integrating cutting-edge technologies are essential to accelerate the translation of fundamental findings into clinical applications and to promote the development of metabolite-centered precision therapeutic strategies.